2021
DOI: 10.1590/0034-737x202168060012
|View full text |Cite
|
Sign up to set email alerts
|

Sample arrangements and spatial variability characterization of dendometrics parameters of Eucalyptus camaldulensis and physical soil attributes

Abstract: Sample arrangements and spatial variability characterization of dendometrics parameters of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 25 publications
(29 reference statements)
0
3
0
Order By: Relevance
“…According to [34], the weak spatial dependence is related to the external factors (e.g., soil tillage and agricultural machinery traffic), while the well-defined spatial dependence is more related to intrinsic factors associated with the natural soil structure. In other similar studies [24,26,44], the authors found spatial dependence of PR in areas under eucalyptus production. However, in these studies, the PR readings were carried out in eucalyptus stands before harvesting and soil tillage.…”
Section: Soil Penetration Resistance In Stand Renewal Areasmentioning
confidence: 52%
See 2 more Smart Citations
“…According to [34], the weak spatial dependence is related to the external factors (e.g., soil tillage and agricultural machinery traffic), while the well-defined spatial dependence is more related to intrinsic factors associated with the natural soil structure. In other similar studies [24,26,44], the authors found spatial dependence of PR in areas under eucalyptus production. However, in these studies, the PR readings were carried out in eucalyptus stands before harvesting and soil tillage.…”
Section: Soil Penetration Resistance In Stand Renewal Areasmentioning
confidence: 52%
“…However, in these studies, the PR readings were carried out in eucalyptus stands before harvesting and soil tillage. Even under these conditions, [26] also observed a decrease in the PR spatial dependence from the bottom to the soil's top layer. In the present study, the geospatial assessment allowed inferences about the spatial distribution of the PR measured after soil tillage.…”
Section: Soil Penetration Resistance In Stand Renewal Areasmentioning
confidence: 90%
See 1 more Smart Citation